Autophagy inhibition perturbs ERBB2 trafficking and abolishes tumorigenesis in ERBB2-driven breast cancer. Issue 4 (3rd April 2021) - Hao, Mingang; Yeo, Syn Kok; Guan, Jun-Lin
ABSTRACT: Macroautophagy/autophagy modulation is increasingly recognized as a potential strategy for cancer therapy. Using a recently developed Rb1cc1 mutant knockin mice model, we have taken a rigorous genetic approach to assess the role of both its autophagy and non-canonical functions in an ERBB2-driven BrCA model. We found that autophagy abrogation virtually abolishes mammary tumorigenesis in the ERBB2-driven model, exhibiting stronger inhibitory effects than in our previous studies using PyMT and brca1 -null mouse models. Mechanistically, autophagy inhibition perturbs ERBB2 intracellular trafficking and triggers its release via small extracellular vesicles. Our results demonstrate a new mechanism for autophagy to promote tumorigenesis in ERBB2-driven BrCA and could supplement current strategies for anti-ERBB2 therapy.